1985
DOI: 10.1111/j.1530-0277.1985.tb05041.x
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated Acetaldehyde Response after Ethanol Administration during Pregnancy and Lactation in Rats

Abstract: The exaggerated blood acetaldehyde response that has been reported after ethanol administration to pregnant rats was found to be the beginning of a much larger alteration occurring during lactation. Indeed, at the end of pregnancy, we confirmed a 4-fold increase in the acetaldehyde values above nonpregnant values after an intragastric dose of 3 g/kg ethanol. During gestational days 1 to 17, the levels did not differ. After delivery, the exaggerated acetaldehyde response to ethanol was increased, producing acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Whether this was due to differences in the nutritional status of the animals or to the ethanol dose administered remains to be seen. However, we found that the metabolism of acetaldehyde after intravenous administration was somewhat retarded in the pregnant animals, in keeping with previous observations (15,26). It is possible that the oral dose of ethanol used in this study (4 g/kg) exceeded the maternal ability to metabolize this compound.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Whether this was due to differences in the nutritional status of the animals or to the ethanol dose administered remains to be seen. However, we found that the metabolism of acetaldehyde after intravenous administration was somewhat retarded in the pregnant animals, in keeping with previous observations (15,26). It is possible that the oral dose of ethanol used in this study (4 g/kg) exceeded the maternal ability to metabolize this compound.…”
Section: Discussionsupporting
confidence: 78%
“…Ethanol is known to cross the placental bamer freely and to be distributed in fetal tissues (12)(13)(14). An exaggerated acetaldehyde response after ethanol administration has been described during pregnancy (15), but it is not certain that acetaldehyde crosses the placenta (15,16). In fact, whereas acetaldehyde administered at high dose to pregnant mice appears to induce teratogenic effects (17), fetal blood acetaldehyde concentrations are always lower than levels in maternal blood, even after high ethanol doses in pregnant rats (18,19).…”
mentioning
confidence: 99%
“…During gestational days 1 to 17, the levels did not differ. After delivery, the exaggerated acetaldehyde response to ethanol was increased, producing acetaldehyde concentrations 15-fold greater than in nonlactating controls [Gordon et al (1985)]. …”
Section: Acetaldehyde Formaldehyde and Breast Cancer Risksmentioning
confidence: 99%
“…During gestational days 1 to 17, the levels did not differ. After delivery, the exaggerated acetaldehyde response to ethanol increased, producing acetaldehyde concentrations 15-fold greater than in nonlactating controls [Gordon et al (1985)]. …”
Section: Relative Risk Data Linking Acetaldehyde/alcohol and Leukemiasmentioning
confidence: 99%